Językowo-kulturowa kreacja skowronka w Pieśni o skowronku Leopolda Staffa - Białoskórska, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article describes—at the level of text—the lexical and semantic determinants of behaviours, attributes, states and conditions as well as the characteristics of the protagonist of the poem. The world presented in the poem was used by the article’s author to depict the symbolic and cultural qualities with which the poet endowed his literary skylark. The analysis of the linguistic layer shows rich metaphorization of the text, varied character of the artistic imaging means composed into the form of a classicistic praise song in honour of the skylark.